Assessment of the analgesic effectiveness of rectus sheath block in patients who had emergency midline laparotomy: Prospective observational cohort study. (2020) - Melesse, Debas Yaregal; Chekol, Wubie Birlie; Tawuye, Hailu Yimer; Denu, Zewuditu Abdissa; Agegnehu, Abatneh Feleke
Abstract: Background: Postoperative pain is a major concern after midline abdominal surgeries. Rectus sheath block (RSB) has been indicated after midline laparatomy; however, the analgesic effect of landmark technique on postoperative pain was not well investigated. Objectives: we tested the hypothesis that RSB reduces pain scores, decreased total analgesic consumption and prolong first analgesic request time after emergency midline laparatomy. Methods: Prospective observational cohort study was done from February 1 to May 10, 2018. Eighty eight patients were observed in this study, 44 in the RSB group and 44 in the non-exposed group. Pain severity was assessed in first 24 h postoperative period in terms of total analgesic consumption, first analgesic request time and visual analogue scale (VAS) score at 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h and 24 h. Results: The RSB group had significantly reduced VAS score at rest and on movement at (1, 2, 4, 6 and 8 h), but not at (10, 12 and 24 h) point assessed. Patients in RSB group had reduced tramadol requirement compared to non-exposed group in 24 h (255.68 ± 80.13) VS (314.77 ± 97.40), P = 0.003). The 24 h diclofenac consumption was significantly lowered in RSB group (75(75–150) than non-exposed group (150(75–150), P = 0.031. Mean time to first analgesic request was significantly longer in RSB group (372.95 ± 131.41) than non-exposed group (50.34 ± 14.12), p ≤ 0.001). Conclusions: The RSB group resulted in less pain scores, reduced total analgesic utilization and stayed for longer time for first analgesic request. Therefore we recommended RSB as part of multimodal analgesia after emergency midline laparatomy. Highlights: The rectus sheath block (RSB) group had significantly reduced VAS score at rest and at movement. Patients in rectus sheath block group had reduced tramadol requirement compared to non-exposed group. The 24 h diclofenac consumption was significantly lowered in RSB group than non-exposed group. Mean time to first analgesic request was significantly longer in RSB group than non-exposed group.